The molecular landscape and associated clinical experience in infant medulloblastoma: prognostic significance of second‐generation subtypes. (1st September 2020) - Hicks, D.; Rafiee, G.; Schwalbe, E. C.; Howell, C. I.; Lindsey, J. C.; Hill, R. M.; Smith, A. J.; Adidharma, P.; Steel, C.; Richardson, S.; Pease, L.; Danilenko, M.; et al.
Abstract : Aims: Biomarker‐driven therapies have not been developed for infant medulloblastoma (iMB). We sought to robustly sub‐classify iMB, and proffer strategies for personalized, risk‐adapted therapies. Methods: We characterized the iMB molecular landscape, including second‐generation subtyping, and the associated retrospective clinical experience, using large independent discovery/validation cohorts (n = 387). Results: iMBGrp3 (42%) and iMBSHH (40%) subgroups predominated. iMBGrp3 harboured second‐generation subtypes II/III/IV. Subtype II strongly associated with large‐cell/anaplastic pathology (LCA; 23%) and MYC amplification (19%), defining a very‐high‐risk group (0% 10yr overall survival (OS)), which progressed rapidly on all therapies; novel approaches are urgently required. Subtype VII (predominant within iMBGrp4 ) and subtype IV tumours were standard risk (80% OS) using upfront CSI‐based therapies; randomized‐controlled trials of upfront radiation‐sparing and/or second‐line radiotherapy should be considered. Seventy‐five per cent of iMBSHH showed DN/MBEN histopathology in discovery and validation cohorts ( P  < 0.0001); central pathology review determined diagnosis of histological variants to WHO standards. In multivariable models, non‐DN/MBEN pathology was associated significantly with worse outcomes within iMBSHH . iMBSHH harboured two distinct subtypes (iMBSHH‐I/II ). Within the discriminated favourable‐risk iMBSHH DN/MBEN patient group, iMBSHH‐II had significantly better progression‐free survival than iMBSHH‐I, offering opportunities for risk‐adapted stratification of upfront therapies. Both iMBSHH‐I and iMBSHH‐II showed notable rescue rates (56% combined post‐relapse survival), further supporting delay of irradiation. Survival models and risk factors described were reproducible in independent cohorts, strongly supporting their further investigation and development. Conclusions: Investigations of large, retrospective cohorts have enabled the comprehensive and robust characterization of molecular heterogeneity within iMB. Novel subtypes are clinically significant and subgroup‐dependent survival models highlight opportunities for biomarker‐directed therapies. Abstract : We characterize the subgroup‐dependent clinico‐molecular landscape of infant medulloblastoma, and also consider the importance of recently‐described subtypes of subgroups. We develop and validate subgroup‐specific survival models and proffer suggestions for the incorporation of subgroup/subtype information into future clinical decision making.